Bioactive potential of nanoparticles of acerola byproduct (Malpighia sp. L): Bioaccessibility in nectar (Research, Society and Development, 2020)
The industrial processing of acerola generates a large amount of waste that is usually discarded, causing economic and environmental losses. Studies show that fruit residues are a rich source of bioactive compounds, which calls attention to new studies to enable the application in food products. In this study, β-carotene, anthocyanins, yellow flavonoids, vitamin C, total extractable polyphenols, and antioxidant activity by the ABTS●+ method were analyzed in the pulp and lyophilized acerola by-product. Therefore, the extract of the acerola by-product was subjected to the spray encapsulation process, using gum arabic and maltodextrin as wall material. The stability of vitamin C, phenolic compounds, and antioxidant activity by ABTS●+ method present in the nanoparticle and antimicrobial activity against the microorganisms E. coli and L. monocytogenes. Finally, the nanoparticle was applied to the nectar and the bioaccessibility for phenolic compounds and antioxidant capacity was verified. The results showed that the pulp and by-product of acerola showed relevant results for polyphenols (1,214.54 mg GAE/100g and 9,802.97 mg GAE/100g, respectively) and vitamin C (1,113.10 mg/100g and 6.039 mg/100 g, in that order). The bioactive compounds and antioxidant activity were maintained in the encapsulated extract, just as the nanoparticle showed bactericidal activity for E. coli. Overall, the results demonstrate the quality of the agroindustrial acerola residue in the form of nanoparticles as a source of bioactive compounds.